Randomized Trial of a Computerized Touch Screen Decision Aid to Increase Acceptance of Colonoscopy Screening in an African American Population with Limited Literacy. Issue 10 (2nd October 2016) - Ruzek, Sheryl B.; Bass, Sarah Bauerle; Greener, Judith; Wolak, Caitlin; Gordon, Thomas F.
ABSTRACT: The goal of this study was to assess the effectiveness of a touch screen decision aid to increase acceptance of colonoscopy screening among African American patients with low literacy, developed and tailored using perceptual mapping methods grounded in Illness Self-Regulation and Information-Communication Theories. The pilot randomized controlled trial investigated the effects of a theory-based intervention on patients' acceptance of screening, including their perceptions of educational value, feelings about colonoscopy, likelihood to undergo screening, and decisional conflict about colonoscopy screening. Sixty-one African American patients with low literacy, aged 50–70 years, with no history of colonoscopy, were randomly assigned to receive a computerized touch screen decision aid (CDA; n = 33) or a literacy appropriate print tool (PT; n = 28) immediately before a primary care appointment in an urban, university-affiliated general internal medicine clinic. Patients rated the CDA significantly higher than the PT on all indicators of acceptance, including the helpfulness of the information for making a screening decision, and reported positive feelings about colonoscopy, greater likelihood to be screened, and lower decisional conflict. Results showed that a touch screen decision tool is acceptable to African American patients with low iteracy and, by increasing intent to screen, may increase rates of colonoscopy screening.